Powerful recombination centers resulting from reactions of hydrogen with carbon–oxygen defects in n‐type Czochralski‐grown silicon (Phys. Status Solidi RRL 8/2017). Issue 8 (18th August 2017) - Vaqueiro‐Contreras, M.; Markevich, V. P.; Halsall, M. P.; Peaker, A. R.; Santos, P.; Coutinho, J.; Öberg, S.; Murin, L. I.; Falster, R.; Binns, J.; Monakhov, E. V.; Svensson, B. G.
Abstract : One of the key characteristics in the materials used for semiconductor device fabrication is their minority carrier lifetime. In the case of silicon‐based solar cells, hydrogen is often introduced during solar cell processing (e.g. from silicon nitride films) for its well‐known passivation capabilities and thus improved lifetime. However, Vaqueiro‐Contreras et al. (article no.1700133 ) have found that hydrogen can interact with carbon–oxygen complexes in phosphorous doped Czochralski grown materials to produce a very powerful recombination centre. This centre has been thoroughly characterized and found to severely decrease the lifetime of photo‐generated carriers in the studied materials, and will therefore reduce the efficiency of the solar cells made from such materials. Even though hydrogen can be dissociated from the complex at relatively low temperatures, the COH complex is expected to reform upon cooling when enough hydrogen is present in the material. These results are of great relevance to the siliconbased solar industry firstly because hydrogen is thought to be advantageous to solar cell fabrication, and secondly because carbon and oxygen are still largely encountered in commercial solar grade silicon which increases the likelihood of a diminished efficiency in the terminated solar cell.